Telaah Literatur: Model Pendidikan Akhlak dalam Pemikiran Pendidikan Islam Klasik dan Modern - Fatakhul Huda (Excelencia: Journal of Islamic Education & Management, 2025)
ABSTRACT This study aims to explore and compare the model of moral education in classical and modern Islamic thought through a library research approach. Classical thinkers such as Al-Ghazali and Ibn Miskawaih emphasize that moral education is a process of purifying the soul (tazkiyah al-nafs) and forming good habits based on divine values. Meanwhile, modern Islamic scholars like Fazlur Rahman and Syed Muhammad Naquib al-Attas view moral education as a rational and spiritual process that helps individuals develop critical awareness, responsibility, and ethical sensitivity in social life. The analysis shows that both classical and modern paradigms share the same goal—to build a complete and virtuous person (insān kāmil)—but they differ in their focus and method. The integration of both perspectives produces a new model of moral education that combines spiritual growth, intellectual understanding, and social involvement. This study contributes to the development of Islamic education and supports the strengthening of character education in contemporary contexts. ABSTRAK Penelitian ini bertujuan untuk mengkaji dan membandingkan model pendidikan akhlak dalam pemikiran Islam klasik dan modern melalui pendekatan studi kepustakaan. Pemikir klasik seperti Al-Ghazali dan Ibn Miskawaih menekankan bahwa pendidikan akhlak merupakan proses penyucian jiwa (tazkiyatun nafs) dan pembentukan kebiasaan baik yang berlandaskan nilai-nilai Ilahi. Sementara itu, tokoh modern seperti Fazlur Rahman dan Syed Muhammad Naquib al-Attas memandang pendidikan akhlak sebagai proses rasional dan spiritual yang membantu seseorang mengembangkan kesadaran kritis, tanggung jawab, serta kepekaan etis dalam kehidupan sosial. Hasil analisis menunjukkan bahwa kedua paradigma memiliki tujuan yang sama, yaitu membentuk manusia yang sempurna dan berakhlak mulia (insān kāmil), tetapi berbeda dalam penekanan metode dan pendekatannya. Integrasi dari kedua pandangan ini menghasilkan model pendidikan akhlak yang menggabungkan pembinaan spiritual, pemahaman intelektual, dan keterlibatan sosial. Kajian ini memberikan kontribusi bagi pengembangan pendidikan Islam dan penguatan pendidikan karakter di era modern.